ACTIVITIES OF THE TROOPS OF THE TURKESTAN MILITARY DISTRICT DURING THE PEOPLE REBELLION OF 1916 IN TURKESTAN (Scientific journal of the Fergana State University, 2023)
The article analyzes the beginning of the popular uprising and protests in Turkestan as a result of the Russian empire’s participation in World War I and the colonial administration was forced to rely on the troops of the Turkestan Military District due to difficulties in suppressing the uprising.